BS ISO 6363-4. Wrought aluminium and aluminium alloys. Cold-drawn rods/bars, tubes and wires. Part 4. Drawn rectangular bars and wires. Tolerances on form and dimensions (9th June 2021) - British Standards Institution,
No abstract available